Can Botulinum Toxin A Still Have a Role in Treatment of Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia Through Inhibition of Chronic Prostatic Inflammation? - Bing-Juin Chiang; Hann-Chorng Kuo; Chun-Hou Liao (Toxins, 2019)
Patients with benign prostatic hyperplasia (BPH) can exhibit various lower urinary tract symptoms (LUTS) owing to bladder outlet obstruction (BOO), prostatic inflammation, and bladder response to BOO. The pathogenesis of BPH involves an imbalance of internal hormones and chronic prostatic inflammation, possibly triggered by prostatic infection, autoimmune responses, neurogenic inflammation, oxidative stress, and autonomic dysfunction. Botulinum toxin A (BoNT-A) is well recognized for its ability to block acetylcholine release at the neuromuscular junction by cleaving synaptosomal-associated proteins. Although current large clinical trials have shown no clinical benefits of BoNT-A for the management of LUTS due to BPH, BoNT-A has demonstrated beneficial effects in certain subsets of BPH patients with LUTS, especially in males with concomitant chronic prostatitis/chronic pelvic pain syndrome and smaller prostate. We conducted a review of published literature in Pubmed, using Botulinum toxin, BPH, BOO, inflammation, LUTS, and prostatitis as the key words. This article reviewed the mechanisms of BPH pathogenesis and anti-inflammatory effects of BoNT-A. The results suggested that to achieve effectiveness, the treatment of BPH with BoNT-A should be tailored according to more detailed clinical information and reliable biomarkers.